Filsafat Agama sebagai Simbiosis Mutualisme Agama dan Filsafat - Huda, Samsul (Media Akademika, 2009)
Religion and philosophy are two entities which have exclusive relation. This paper is going to analyze the symbiosis of mutualism between religion and philosophy. The synergy both of them scientifically appearing the philosophy of religion as the science which has the numerous roles in methodology of religion studies in modern age and globalization era .